Supporting the “forgotten” ventricle: The evolution of percutaneous RVADs - James, Les; Smith, Deane E. (Frontiers in Cardiovascular Medicine, 2023)
Right heart failure (RHF) can occur as the result of an acute or chronic disease process and is a challenging clinical condition for surgeons and interventionalists to treat. RHF occurs in approximately 0.1% of patients after cardiac surgery, in 2–3% of patients following heart transplantation, and in up to 42% of patients after LVAD implantation. Regardless of the cause, RHF portends high morbidity and mortality and is associated with longer hospital stays and higher healthcare costs. The mainstays of traditional therapy for severe RHF have included pharmacological support, such as inotropes and vasopressors, and surgical right ventricular (RV) assist devices. However, in recent years catheter-based mechanical circulatory support (MCS) strategies have offered novel solutions for addressing RHF without the morbidity of open surgery. This manuscript will review the pathophysiology of RHF, including the molecular underpinnings, gross structural mechanisms, and hemodynamic consequences. The evolution of techniques for supporting the right ventricle will be explored, with a focus on various institutional experiences with percutaneous ventricular assist devices.